Context counts: The different implications of weekday and weekend video gaming for academic performance in mathematics, reading, and science - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2018)
Video gaming has been a source of serious concern for parents and educators, based on the belief that video games disrupt adolescents' academic activities. However, previous studies have been mixed regarding video games’ effects on academic outcomes. We revisited this issue by analyzing data on approximately 30,000 adolescents from three large-scale public datasets. We consistently found that the more adolescents played video games on weekdays, the poorer they performed on standardized assessments of mathematics, reading, and science. In contrast, weekend video gaming was positively associated with academic performance. Our findings suggest that weekday and weekend video gaming may be differentially associated with academic outcomes, depending on the context in which it occurs.